Tenure: Policy research on resources, rights, and equity - Meinzen-Dick, Ruth S.; Lambrecht, Isabel B.; Place, Frank; Chigbu, Uchendu Eugene; Monterroso, Iliana; Suhardiman, Diana (International Food Policy Research Institute, 2025)
Secure tenure of land and natural resources is critical for ensuring equitable, efficient, and sustainable production of food and resilient rural livelihoods. This chapter examines foundational concepts and key lessons from research on tenure, including how different forms of tenure affect investment in production and resource management, and identifies priorities for further study, policy, and practice.